1991
DOI: 10.1017/s0022029900029988
|View full text |Cite
|
Sign up to set email alerts
|

Influence of milk flow rate and streak canal length on new intramammary infection in dairy cows

Abstract: Eighteen cows with a wide range of quarter peak flow rates (O35-2-22 kg/min) were inoculated with Streptococcus agalactiae and Str. dysgalactiae 4 mm into each streak canal every 3 d for 12 d. Thirty of the 72 quarters developed intramammary infection. Mean peak flow rate and length of streak canal of those quarters that became infected were 1-26 + 0-08 kg/min (mean + SEM) and 11-47±0-41 mm respectively, compared with 101 + 0 0 5 kg/min and 1205±035 mm for those that remained uninfected. Logistic regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
15
4
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 7 publications
4
15
4
1
Order By: Relevance
“…Mean values of the parameters are different from those reported earlier (McDonald, 1968a ;Grindal et al 1991;Hamana et al 1994) especially in the longer teat canal. These outcomes are explained by the use of different kinds of methods and mechanical manipulation of the teats to be examined.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Mean values of the parameters are different from those reported earlier (McDonald, 1968a ;Grindal et al 1991;Hamana et al 1994) especially in the longer teat canal. These outcomes are explained by the use of different kinds of methods and mechanical manipulation of the teats to be examined.…”
Section: Discussioncontrasting
confidence: 74%
“…Natural defence mechanisms against udder pathogens are the teat and teat connective tissue. The influence of teat canal length and diameter on the occurrence of mastitis by bacterial pathogens has been examined (McDonald, 1975;Grindal et al 1991;Scherzer, 1992;Seyfried, 1992;Hamana et al 1994 ;Lacy-Hulbert & Hillerton, 1995). Grindal et al (1991) could find no significant influence of teat canal length on new infection McDonald (1975) and Hamana et al (1994) but, additionally, they found significant differences in teat canal diameter between healthy and infected udder quarters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study showed that CL was longer (1.74 cm) in healthy udders than in infected udders (1.58 cm), and that CL and the number of lactations were related to the CMT score of the cows 10 . Others reported the CL as 1.14 ± 0.41 cm in infected teats and 1.20 ± 0.35 cm in non‐infected teats, 20 and Gulyas and Ivancsics found a positive correlation between CL and somatic cell count 28…”
Section: Discussionmentioning
confidence: 99%
“…Other advantages of ultrasonography for evaluating intramammary tissues are its ease of use and being non‐invasive 8,12,16–18 . Ultrasonographic techniques can be used to determine the intramammary factors that may lead to the development of mastitis and these factors should be taken into consideration in the control and prevention of mastitis 13,16,19–22 …”
mentioning
confidence: 99%